PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN CV. SUMBER REZEKI - Hery Wihasnato (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
This study aims to determine the effect of job satisfaction and motivation on employee productivity at CV. Sumber Rezeki. Researchers used quantitative descriptive research methods in this study. The results obtained are based on a questionnaire. Job satisfaction and partial motivation have a positive and significant effect on employee productivity at CV. Sumber Rezeki. While job satisfaction and motivation simultaneously have a positive and significant effect on employee productivity at CV. Sumber Rezeki based on the results of data processing. So it can be concluded that job satisfaction and motivation have a positive and significant effect on productivity.